STUDY ON SEPARATION OF 137Cs FROM 235U FISSION PROCESS WASTE. UTILIZATION OF SILICA GEL-SUPPORTED FERROCYANIDE COMPLEX SALT FOR 137Cs PICKING - Sunarhadijoso Soenarjo; Anung Pujianto (PTBN - BATAN, 2008)
ABSTRACT STUDY ON SEPARATION OF 137Cs FROM 235U FISSION PROCESS WASTE. UTILIZATION OF SILICA GEL-SUPPORTED FERROCYANIDE COMPLEX SALT FOR 137Cs PICKING. In connection with the potential domestic demand especially in the fields of industry and nuclear medicine, the separation of 137Cs from 235U fission process waste is to be of interest although its economic value could be a polemic. A preliminary study on the separation of 137Cs from the 235U fission process waste generated in the production of 99Mo in P.T. BATAN Teknologi, Serpong, was performed through experiments on 137Cs picking from sample solution of the radioactive fission waste (RFW). The presented study is aimed to gain experimental data supporting utilization of the matrix of silica gel-supported ferrocyanide complex salt for the separation of 137Cs from RFW. Subsequent step would be the recovery and purification of 137Cs as part of production technology of 137Cs. The RFW sample was batch-treated with the matrix of silica gel-supported ferrocyanide complex salt which was synthesized from silica gel, potassium hexacyanoferrate(II) and copper(II) chloride. The binding of radioisotopes in RFW on the matrix was observed by y-spectrometry of the RFW solution before and during the treatment. The results showed that approximately 85% of 137Cs could be picked from the RFW sample into the matrix. Less amount of 95Zr and 95Nb was bound into the matrix. 103Ru was slightly bound into the matrix whereas 141/144Ce and 129mTe were not. It was observed that by using 0.2 and 0.4 g of matrix for 10 ml of RFW, the amount of matrix influenced the binding quantity of 95Zr and 95Nb but not that of 137Cs. FREE TERMS: Separation of 137Cs, 235U fission process, Ferrocyanide complex salt, Radioactive fission waste (RFW), y-spectrometry ABSTRAK STUDI PEMISAHAN 137Cs DARI LIMBAH PROSES FISI 235U. PENGGUNAAN MATRIK SILIKA GEL-GARAM KOMPLEK FEROSIANIDA UNTUK PEMUNGUTAN 137Cs. Berkaitan dengan potensi kebutuhan domestik, terutama di bidang industri dan kedokteran nuklir, pemisahan 137Cs dari limbah proses fisi 235U menjadi hal yang menarik walaupun mungkin masih menjadi perdebatan apakah ekonomis atau tidak. Sebagai studi awal untuk pemisahan 137Cs dari limbah proses fisi 235U, telah dilakukan percobaan pemungutan 137Cs dari cuplikan limbah radioaktif proses fisi (radioactive fission waste, RFW) yang dihasilkan pada proses produksi 99Mo di P.T. BATAN Teknologi, Serpong. Percobaan ini bertujuan untuk mendapatkan data eksperiment yang mendukung penggunaan matrik silika gel-garam komplek ferosianida untuk memisahkan 137Cs dari RFW. Tahapan selanjutnya adalah pemungutan dan pemurnian 137Cs sebagai bagian dari teknologi produksi 137Cs. Cuplikan RFW diperlakukan dalam proses batch dengan matrik silika gel-garam komplek ferosianida yang dibuat dari silika gel, kalium heksasianoferat(II) dan tembaga(II) klorida. Pengikatan radioisotop dalam RFW pada matrik diamati dengan teknik spektrometri- terhadap larutan RFW sebelum dan selama perlakuan dengan matrik. Hasil percobaan menunjukkan bahwa sekitar 85% 137Cs dapat terambil dari larutan RFW dan terikat pada matrik. Dalam kuantitas yang lebih rendah, radionuklida 95Zr dan 95Nb juga dapat terikat pada matrik. Radionuklida 103Ru terikat pada matrik dalam jumlah yang relatif kecil sedangkan radionuklida 141/144Ce dan 129mTe tidak terikat. Dengan menggunakan 0,2 dan 0,4 gram matrik untuk perlakuan terhadap 10 ml larutan RFW, dapat diamati adanya pengaruh jumlah matrik terhadap kuantisasi pengikatan 95Zr dan 95Nb tetapi tidak terhadap pengikatan 137Cs. KATA KUNCI: Pemisahan 137Cs, Proses fisi 235U, Garam komplek ferosianida, Limbah radioaktif proses fisi (RFW), Spektrometri-